(untitled) (Global Journal of Science Frontier Research, 2012)
In this article, we are discussing the Gauss’s law used to determine the width emitter extension region of the solar cell operating in open circuit condition. Taking into account the grain size (g), the grain boundary recombination velocity (Sgb) and the emitter doping density (Nemitter), the Gaussian Law helped us to calculate the width emitter extension region of the solar cell operating in open circuit condition. To determine the width emitter extension region, we first showed that grain size (g), grain boundary recombination velociy (Sgb) are oppesite effects and concluded that best solar cells are characterized by low junction extension region width observed only with high grain size (g) and low grain boundary recombination velocity (Sgb).